PEMANFAATAN LAHAN PEKARANGAN UNTUK MENDUKUNG KETAHANAN PANGAN KELUARGA - Wening Tyas; Annisa Nur Azizah; Muhammad Habib Assyqin; Devi Kuernianti (Jurnal Abdi Insani, 2025)
Household food security is a crucial issue influenced by limited land and food price fluctuations. Home garden utilization is considered an effective strategy to increase healthy food availability, reduce market dependence, and support family nutrition. Harapan Jaya Village, Semendawai Timur Sub-district, OKU Timur Regency has underutilized home gardens, thus requiring intervention through a community service program. The aim of this program was to improve the knowledge and skills of housewives in managing productive home gardens to support household food security. The method consisted of four main stages: preparation (problem identification, seed procurement, material development, and coordination), counseling (education on benefits and simple cultivation techniques), implementation (distribution of chili peppers, green eggplants, and purple eggplants accompanied by planting practice), and mentoring (regular monitoring together with students of KKN 24 Universitas Nurul Huda). The results showed an increase in participants’ understanding and skills in simple vegetable cultivation. Most of the distributed seedlings grew well and were utilized for family consumption. Some participants even expanded their gardens by planting additional vegetables such as spinach and kale. Active community participation and support from village officials were key success factors of the program. In conclusion, this program effectively encouraged the optimization of home gardens as a source of healthy family food. For sustainability, it is recommended to establish a Women Farmers Group (KWT) as a learning forum, provide training on product processing and marketing, and introduce crop diversification with simple technologies such as verticulture